2018
DOI: 10.1038/s41598-018-31808-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper mediated amyloid-β binding to Transthyretin

Abstract: Transthyretin (TTR), a homotetrameric protein that transports thyroxine and retinol both in plasma and in cerebrospinal (CSF) fluid provides a natural protective response against Alzheimer’s disease (AD), modulates amyloid-β (Aβ) deposition by direct interaction and co-localizes with Aβ in plaques. TTR levels are lower in the CSF of AD patients. Zn2+, Mn2+ and Fe2+ transform TTR into a protease able to cleave Aβ. To explain these activities, monomer dissociation or conformational changes have been suggested. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…The X-ray crystal structure analysis of TTR in complex with Mn 2+ did not show any significant structural differences. Two possible Mn 2+ binding sites were detected around Asp99 and Glu66 in monomer A, and two, Glu66 and Asn98, in monomer B, Figure 4b [52]. In contrast, when wt-TTR crystals were treated with Cu 2+ , these displayed a similar behavior of those soaked with Fe 2+ (Figure 4a) and Re 2+ [31,52].…”
Section: Cu 2+ Fe 2+ and Mn 2+mentioning
confidence: 92%
“…The X-ray crystal structure analysis of TTR in complex with Mn 2+ did not show any significant structural differences. Two possible Mn 2+ binding sites were detected around Asp99 and Glu66 in monomer A, and two, Glu66 and Asn98, in monomer B, Figure 4b [52]. In contrast, when wt-TTR crystals were treated with Cu 2+ , these displayed a similar behavior of those soaked with Fe 2+ (Figure 4a) and Re 2+ [31,52].…”
Section: Cu 2+ Fe 2+ and Mn 2+mentioning
confidence: 92%
“…In 2018, it has been hypothesized that the TTR-Aβ interaction was modulated by metal ions. Different experiments were performed using bio-layer interferometry (BLI) between TTR and the biotinylated peptide Aβ (1-28) with various CuCl 2 concentration (0-12.5 mM) and the results showed that the affinity of TTR for Aβ (1-28) is modulated by copper [138]. Moreover, the crystal structures of TTR obtained in presence of Cu 2+ and Fe 2+ showed a conformational change comparable to that found for the TTR-rhenium complex in which the distances between L110 and L110' increased up to 8.5 Å in one T4-BP, while decreased in the other probably due to the rhenium binding [139].…”
Section: β-Amyloid-binding Sites On Ttrmentioning
confidence: 99%
“…While the main component is Aβ, up to 488 other proteins that also influence the process of aggregation have been detected [ 6 ]. For example, a cross-reaction with apolipoprotein A1, cystatin C, or transthyretin inhibits amyloid formation [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, the formation of pathogenic Aβ peptides can be avoided through the cleavage of APP by α-secretase and the release of soluble APPα (sAPPα) (a process referred to as the non-amyloidogenic pathway; Figure 1 ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%